GROWTH AND INDUSTRIAL POLICY DURING TRANSITION - Cerovic, Bozidar; Nojkovic, Aleksandra; Uvalic, Milica (Economic Annals, 2014)
After twenty-five years of economic transition economic performance varies considerably in transition countries, while in most cases current outcomes show that the desired effects have not been achieved. In this paper we elaborate on why industrial policy has been a key missing element in the transition and has greatly contributed to the unexpectedly small and slow pace of economic recovery. After discussing the achieved level of economic development we undertake an empirical analysis in order to define the role of several important factors of growth, as seen at the beginning of transition (reform progress, macroeconomic stabilisation, initial conditions) and those that attracted particular attention during the global crisis (industrial/manufacturing output, exports). The analysis shows that the growth model in transition economies has altered both over time and in relation to the progress of transition reforms. The most important change concerns the share of industrial output in GDP, which is found to be one of the most important factors of growth after the initial phase of reform. These results suggest that transition economies should implement industrial policy measures as an integral part of their reform strategy instead of just speeding up reforms as the key (if not the only) element of government policy. Based on these results, we explore what would be a viable and proper industrial policy in transition countries, particularly what should be done in current conditions after the damaging effects of the recurrent global recession, and make some policy suggestions.